Association between radiotherapy for surgically treated oral cavity cancer and secondary lung cancer - Dongjie He; Jun Zhang; Ying Xiang; Peiwen Wu; Gaiyan Li; Hao Chang; Qiming Wang; Qiuju Shao; Siying Zhu (Frontiers Media S.A., 2023)
BackgroundThere is limited research on the incidence of secondary lung cancer (SLC) after radiotherapy (RT) for oral cavity cancer (OCC). Therefore, we investigated the association between RT for OCC and the risk of SLC and the overall survival of these patients.MethodsPatients diagnosed with OCC between 1975 and 2015 were selected from the Surveillance, Epidemiology, and End Results database. The cumulative incidence of SLC, relative risk (RR) of RT vs. no RT (NRT), standardized incidence ratios (SIR), and survival outcomes were assessed.ResultsA total of 10,936 patients with OCC were included. Of these, 429 (3.92%) patients developed SLC, where 136 (5.02%) received RT and 293 (3.56%) did not. The cumulative incidence of SLC during follow-up was 6.89% and 4.84% in the RT and NRT patients, respectively. RT was associated with a higher risk of SLC. In the subset analysis, the results showed that a higher risk of developing SLC among patients with index OCC in most subgroups. Dynamic RR and SIR revealed a decreased risk of SLC with increasing latency time. No difference was observed in the 10-year survival rates for patients with SLC who received RT or not or compared with primary lung cancer.ConclusionRT was associated with a higher risk of SLC, and patients diagnosed with OCC could be followed for 5-10 years after diagnosis.